Filter Synthesis Using Genesys S - Rhea, Randall W. (Artech House microwave library., 2014)
S/Filter includes tools beyond direct synthesis, including a wide variety of both exact and approximate equivalent network transforms, methods for selecting the most desirable out of potentially thousands of synthesized alternatives, and a transform history record that simplifies design attempts requiring iteration. Very few software programs are based on direct synthesis, and the additional features of S/Filter make it a uniquely effective tool for filter design. This resource presents a practical guide to using Genesys software for microwave and RF filter design and synthesis. The focus of the book is common filter design problems and how to use direct synthesis to solve those problems. This book covers the application of S/Filter features to solving important and common filter problems. Both lumped element and distributed filters are discussed, with extensions to dielectric and quartz crystal resonators.